Post-Apartheid reading of Jeremiah 8:18-9:22 : an approach for inter- generational healing - Groenewald, Alphonso, 1969- (University of Pretoria, 2024)
Dissertation (MTh (Biblical Studies Old Testament))--University of Pretoria, 2023.